PENGARUH PEMBELAJARAN DARING TERHADAP MINAT BELAJAR MAHASISWA PADA MASA PANDEMIK COVID-19 - Syarifah Hikmah Jamil; Invony Dwi Aprilisanda (BAJ: Behavioral Accounting Journal, 2020)
Pandemics that hit the world including Indonesia had an impact on all sectors, including the Education sector. This has an impact with the introduction of distance learning with an online learning system. Because of this distance system the lecturer is required to be able to convey the course material well to students. This study aims to determine whether online learning carried out by lecturers at INSTIKA and UPN East Java can increase students' interest in studying the courses they tidake. The sample used in this study were 278 students. The analytical tool used was IBM SPSS Version 21. The results showed that the attitude of internet use, perception, experience, financial condition significantly influenced students' interest in learning. While the ability to learn independently does not have a significant effect on student interest in learning during online lectures.